Piezoresistive sensor based on coaxial electrospinning matrix grafted growth of thorny polypyrrole conductive phase and preparation method thereof
By grafting the growth of the spiny polypyrrole conductive phase on the microfiber membrane with a core of high Tg material using coaxial electrospinning technology, the problems of weak and poor stability of existing sensors are solved, and a flexible pressure sensor with high stability and sensitivity are achieved.
Patent Information
- Application Number
- CN202410630220.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-21
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-05-21
AI Technical Summary
When existing flexible pressure sensors grow conductive phases in situ on the elastomeric matrix, the bonding is weak, the stability is poor, and the conductive phase is uneven, which affects the life and consistency of the sensor.
The spiked polypyrrole conductive phase is grown in situ on the micron fiber membrane in the inner core of the high Tg material by coaxial electrospinning technology, and a stable conductive fiber membrane is formed by dopamine as a chemical binder and grafting agent.
The conductive phase is uniformly grown on high Tg materials, which improves the stability and sensitivity of the sensor, extends the life of the sensor, and improves the simplicity of the preparation method and signal cycle stability.
Smart Images

Figure CN118583333B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of sensor technology and relates to a piezoresistive sensor, and in particular to a piezoresistive sensor based on a coaxial electrospinning matrix grafted with a thorny polypyrrole conductive phase and a preparation method thereof. The sensor preparation method is simple and has good signal cycle stability, and can be used in the field of high-precision and high-weather-resistance sensing. Background Art
[0002] In recent years, the market demand for wearable devices related to artificial intelligence has become increasingly strong. More and more devices have realized the integration and intelligence of sensors to detect special signals, driving the rapid rise of research and development and application of flexible pressure sensors, one of the core components, in different fields. Thanks to the large specific surface area and a large number of fiber-fiber contact sites of electrospun fibers, the in-situ growth of conductive phases on the surface of electrospun fibers is expected to prepare high-performance flexible pressure sensors, which can be used to monitor local physiological signs such as renal pelvic pressure in the body. However, when the conductive phase is grown in situ directly on the surface of the elastomer matrix, the two are only bonded by hydrogen bonds, the bond is weak, and it is easy to delaminate. In addition, the morphology of most conductive phases is not uniform, and the polymer elastomer matrix is prone to creep. Problems such as diameter still plague the academic community, resulting in poor stability and short life of the final composite conductive fiber membrane, and poor consistency between the prepared devices. The present invention provides a piezoresistive sensor based on a coaxial electrospinning matrix grafted with a thorny polypyrrole conductive phase and a preparation method thereof, which can ensure that the conductive phase grows in a uniform morphology on a coaxial fiber with a high Tg material inner core, and maintains a certain stability under the condition of ensuring sensitivity, thereby greatly promoting the industrialization of flexible pressure sensors in many fields. Summary of the invention
[0003] The purpose of the present invention is to provide a piezoresistive sensor based on a coaxial electrospinning matrix grafted with a thorny polypyrrole conductive phase and a preparation method thereof; the sensor is light in weight, easy to manufacture and has good signal cycle stability, and can be used for real-time monitoring of high-precision, high-weather resistance scenarios.
[0004] The piezoresistive sensor based on the coaxial electrospinning matrix grafted growth of thorny polypyrrole conductive phase includes a pressure-sensitive layer, an electrode layer and a packaging layer. The pressure-sensitive layer is a conductive fiber membrane obtained by in-situ dopamine chemical grafting growth of thorny polypyrrole conductive phase on a micron fiber membrane matrix; the micron fiber membrane is prepared by coaxial electrospinning. The electrode layer is made by screen printing silver paste on a polyester film according to a customized electrode pattern.
[0005] In the above technical solution, further, the micron fiber membrane matrix is prepared by coaxial electrospinning with a thermoplastic polyurethane elastomer as the outer shell and a high Tg polymer as the inner core; the high Tg polymer is one or more of polyethersulfone and polyimide.
[0006] Further, the coaxial electrospinning is:
[0007] Every 6-10g of polyurethane elastomer is dissolved in a mixed solvent of 20g of N,N-dimethylformamide and 20g of tetrahydrofuran by an ultra-speed mixer to form a first uniform spinning solution with a solid content of 14-20wt%, and every 10-12g of high Tg polymer is dissolved in a mixed solvent of 30g of N-methylpyrrolidone and 10g of tetrahydrofuran by an ultra-speed mixer to form a second uniform spinning solution with a solid content of 17-25wt%; under the spinning conditions of a voltage of 12-20kv, a pushing speed of 0.001-0.003mm / s, and a receiving distance of 7cm, the first uniform spinning solution is used as the outer shell, the second uniform spinning solution is used as the inner core, and a coaxial needle is used to obtain a micron fiber membrane with an average thickness of 100-300μm. Compared with the traditional electrospinning method, the traditional electrospinning is combined with the surface grafting process. The pure elastomer will lead to poor sensor stability, and there will be problems such as interface mismatch between the pure high Tg material and the subsequent conductive phase, which will make the sensor extremely easy to damage under flexible application conditions (such as bending and twisting). The technical solution of the present invention does not have the problem of interface detachment, and has a high Tg material as the inner core, and the stability has been greatly improved.
[0008] Furthermore, the preparation method of the conductive fiber membrane is as follows:
[0009] Dopamine was dissolved in deionized water, and then pyrrole monomer was added, and magnetic stirring was performed for 30 minutes until all the monomers were dissolved to obtain solution a, which was placed in an environment of 0-6°C for 5 minutes;
[0010] Take the micron fiber membrane and soak it in solution a. After it is completely soaked, place it in an environment of 0-6°C for at least 12 hours. Then add ferric chloride powder into deionized water, stir it magnetically for 30 minutes until it is completely dissolved, add a certain amount of hydrochloric acid solution and continue stirring for 30 minutes. After standing in an environment of 0-6°C for at least 1 hour, obtain solution b.
[0011] Under low temperature conditions, solution b is added dropwise into solution a, and the reaction is continued in an environment of 0-6°C for at least 12 hours. Then, the fiber membrane after the growth of the conductive phase is ultrasonically cleaned and dried.
[0012] Among the above-mentioned ambient temperatures, 4-5°C is preferred.
[0013] The present invention uses dopamine as a chemical adhesive. Compared with the traditional method using dodecylbenzene sulfonic acid, dodecylbenzene sulfonic acid has only hydrogen bonds between the conductive phase and the matrix, while dopamine has chemical bonds, which is more stable and has no interface problems. Moreover, only with the participation of dopamine can pyrrole be polymerized into a thorn-like structure, which is an indispensable step in this experiment. By adding hydrochloric acid, hydrogen ions are added to the reaction environment. Hydrogen ions can make it easier for pyrrole to form α-α bonds during polymerization, and can make the polypyrrole chain more inclined to straighten rather than agglomerate. This is also the theoretical basis for macroscopic generation of thorn-like structures.
[0014] Furthermore, the molar ratio of the dopamine monomer to the pyrrole monomer is 2:1, and the molar ratio of the ferric chloride to the pyrrole monomer is 2:5.
[0015] Furthermore, the concentration of the dopamine monomer is 0.02 mol / L, the concentration of the pyrrole monomer is 0.2 mol / L, and the concentration of the hydrochloric acid is 2 mol / L.
[0016] Furthermore, the conductivity of the conductive fiber membrane is in the range of 0.1-2S / m.
[0017] Furthermore, it is characterized in that the thickness of the conductive fiber membrane is 0.1-0.3 mm.
[0018] The pressure-sensitive principle of the piezoresistive sensor is that a uniform thorny polypyrrole conductive phase is in situ grafted on the coaxial micron fiber membrane substrate based on dopamine chemical grafting growth. Under different pressures, the fibers grafted with the thorny conductive phase show different effective resistances due to different contacts, thereby achieving sensing. The purpose of preparing the pressure sensor by electrospinning is to increase the contact points when in contact with each other, and the thorny structure can significantly increase the pressure points under pressure, thereby improving sensitivity.
[0019] The beneficial effects of the technical solution of the present invention are:
[0020] The present invention provides a piezoresistive sensor based on coaxial electrospinning matrix grafted growth of thorny polypyrrole conductive phase and a preparation method thereof. The sensor preparation method is simple and has good signal cycle stability, and has great potential and advantages in the field of high-precision and high-weatherability sensing. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the process of preparing a piezoresistive sensor in an embodiment of the present invention.
[0022] Figure 2 This is a schematic diagram of the principle of in-situ polymerization growth of thorny polypyrrole on the surface of the coaxial electrospun fiber membrane in an embodiment of the present invention.
[0023] Figure 3In the embodiments of the present invention: i) is a SEM image of an electrospun fiber membrane; ii) is a SEM image of a conductive phase grafted onto a fiber membrane; iii) is a TEM image of a cross-section of the fiber membrane.
[0024] Figure 4 The SEM images and conductivity of polypyrrole grown in situ on the coaxial fiber surface at different DA monomer concentrations in the embodiment of the present invention are shown in FIG.
[0025] Figure 5 The SEM images and electrical conductivity of polypyrrole grown in situ on the coaxial fiber surface at different pyrrole monomer concentrations in the embodiment of the present invention are shown in FIG.
[0026] Figure 6 It is the response signal platform of the sensor under different loads in the embodiment of the present invention.
[0027] Figure 7 It is the 10,000-second cycle stable signal of the sensor at a frequency of 1 Hz in the embodiment of the present invention.
[0028] Figure 8 The SEM image of the fiber membrane surface after the conductive phase is grown under non-acidic conditions in the embodiment of the present invention, its molecular dynamics simulation results, and the device test results after preparation in a non-hydrochloric acid environment. DETAILED DESCRIPTION
[0029] The present invention will be further described below with reference to the accompanying drawings and specific embodiments:
[0030] In the following examples, TPU@PES coaxial electrospun fiber membrane was prepared by the following method:
[0031] Thermoplastic polyurethane elastomer (TPU) is dissolved in solvent one and stirred to dissolve to prepare electrospinning solution; solvent one is usually a mixture of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) solution in a ratio of 1:1. The mass concentration of the spinning solution can usually be 14%. Polyethersulfone (PES) is dissolved in solvent two and stirred to dissolve to prepare electrospinning solution; solvent two is usually a mixture of tetrahydrofuran (THF) and N-methylpyrrolidone (NMP) solution in a ratio of 1:3. The mass concentration of the spinning solution can usually be 20%. Coaxial spinning is performed using a coaxial spinning needle with PES as the inner core and TPU as the outer shell. After spinning, the fiber membrane is removed and placed in a vacuum drying oven for drying; the parameters can be as follows: the voltage is 12-20kV, the flow rate of the two spinning solutions is 3.6mL / h, the distance between the needle tip and the roller receiver is 7-12cm, the ambient temperature is 10-30℃, and the relative humidity is 20-80%. In the step of in situ growth of polypyrrole on the fiber surface, the fiber membrane is preferably immersed in a dopamine monomer and pyrrole monomer solution and stored in a low temperature environment of 0-6°C for 12 hours, and the acidic oxidant solution is stored in a low temperature environment of 0-6°C for at least 1 hour. After the two are mixed, they are stored in a low temperature environment of 0-6°C for at least 12 hours to allow them to react fully.
[0032] The pressure sensing test method of the composite conductive fiber membrane is as follows: the conductive fiber membrane is cut into discs with a diameter of 1 cm, placed on glass with screen-printed silver electrodes, a push-pull force gauge is used to apply pressure to the conductive fiber membrane, and a digital source meter is used to read the resistance value of the conductive fiber membrane under the pressure.
[0033] Embodiment 1:
[0034] 1. First, 6g of polyurethane was dissolved in a mixed solvent of 18g of N,N-dimethylformamide (DMF) and 18g of tetrahydrofuran (THF) to form a uniform spinning solvent with a solid content of 14wt%; 10g of polyethersulfone was dissolved in a mixed solvent of 27g of N-methylpyrrolidone (NMP) and 9g of tetrahydrofuran (THF) to form a uniform spinning solvent with a solid content of 20wt%. Under the spinning conditions of 15kv voltage, 0.001mm / s pushing speed and 7cm receiving distance, a spinning fiber membrane with an average thickness of 150μm was obtained.
[0035] 2. Weigh 0.06 g of dopamine hydrochloride and place it in beaker a containing 20 mL of deionized water to dissolve, add a magnet and stir on a magnetic stirrer until the solid is completely dissolved; then add 280 μL of pyrrole monomer to the above solution, and stir magnetically again until the solid is completely dissolved; finally, cut a 2*2 cm electrospun membrane and place it in a culture dish, add the solution in beaker a to completely soak it, and place it in a 4°C refrigerator for 12 hours.
[0036] 3. Dissolve 2.5g of ferric chloride hexahydrate in beaker b containing 20mL of deionized water, and add 3.4ml of hydrochloric acid drop by drop, stirring magnetically until it is completely dissolved. After placing in the refrigerator for 1 hour, add the solution in beaker b drop by drop with a dropper to the above culture dish, continue to react at 4℃ for 12 hours, then wash after ultrasonication and dry.
[0037] 4. Cut the conductive fiber membrane into 1 cm diameter discs and place them on glass with screen-printed silver electrodes. Use a push-pull force gauge to apply pressure to the conductive fiber membrane. Use a digital source meter to read the resistance value of the conductive fiber membrane under the pressure. The response signal platform under different loads is as follows: Figure 6 shown.
[0038] Embodiment 2:
[0039] Comparison using pyrrole monomer concentration as a variable
[0040] 1. First, 6g of polyurethane was dissolved in a mixed solvent of 18g of N,N-dimethylformamide (DMF) and 18g of tetrahydrofuran (THF) to form a uniform spinning solvent with a solid content of 14wt%; 10g of polyethersulfone was dissolved in a mixed solvent of 27g of N-methylpyrrolidone (NMP) and 9g of tetrahydrofuran (THF) to form a uniform spinning solvent with a solid content of 20wt%. Under the spinning conditions of 15kv voltage, 0.001mm / s pushing speed and 7cm receiving distance, a spinning fiber membrane with an average thickness of 150μm was obtained.
[0041] 2. Prepare seven groups of samples, weigh 0.06g of dopamine hydrochloride in each sample and place it in beaker a filled with 20mL of deionized water to dissolve, add a magnet and stir on a magnetic stirrer until the solid is completely dissolved; then add 0μL, 70μL, 210μL, 280μL, 350μL, 420μL, and 560μL of pyrrole monomer to the above solution, respectively, and stir magnetically again until the solid is completely dissolved; finally, cut a 2*2cm electrospun membrane and place it in a culture dish, add the solution in beaker a to completely soak it, and place it in a 4℃ refrigerator for 12h.
[0042] 3. Dissolve 2.5g of ferric chloride hexahydrate in beaker b containing 20mL of deionized water, and add 3.4ml of hydrochloric acid drop by drop, stirring magnetically until it is completely dissolved. After placing in the refrigerator for 1 hour, add the solution in beaker b drop by drop into each of the above culture dishes with a dropper, continue to react at 4℃ for 12 hours, then wash after ultrasonication and dry.
[0043] 4. Cut a small piece from the prepared sample, stick it on a carbon tape, spray gold, and place it in a field emission scanning electron microscope to observe the morphology of the in-situ grown polypyrrole conductive layer on the coaxial fiber surface. Figure 5As shown in the figure, with the increase of pyrrole monomer concentration, thorny polymers gradually began to appear on the fiber surface and gradually became dense, and with the continuous increase of concentration, many free polypyrrole fibers appeared. The prepared composite conductive fiber membrane was tested for conductivity, as shown in the figure. Figure 5 shown.
[0044] Embodiment 3:
[0045] Comparison using dopamine (DA) monomer concentration as a variable
[0046] 1. First, 6g of polyurethane was dissolved in a mixed solvent of 18g of N,N-dimethylformamide (DMF) and 18g of tetrahydrofuran (THF) to form a uniform spinning solvent with a solid content of 14wt%; 10g of polyethersulfone was dissolved in a mixed solvent of 27g of N-methylpyrrolidone (NMP) and 9g of tetrahydrofuran (THF) to form a uniform spinning solvent with a solid content of 20wt%. Under the spinning conditions of 15kv voltage, 0.001mm / s pushing speed and 7cm receiving distance, a spinning fiber membrane with an average thickness of 150μm was obtained.
[0047] 2. Prepare seven groups of samples, weigh 0g, 0.015g, 0.03g, 0.045g, 0.06g, 0.075g, and 0.09g of dopamine hydrochloride for each sample, respectively, and place them in beaker a filled with 20mL of deionized water to dissolve, add a magnet and stir on a magnetic stirrer until all the solids are dissolved; then add 280μL of pyrrole monomer to the above solutions, and stir magnetically again until all the solids are dissolved; finally, cut a 2*2cm electrospun membrane and place it in a culture dish, add the solution in beaker a to completely soak it, and place it in a 4℃ refrigerator for 12h.
[0048] 3. Dissolve 2.5g of ferric chloride hexahydrate in beaker b containing 20mL of deionized water, and add 3.4ml of hydrochloric acid drop by drop, stirring magnetically until it is completely dissolved. After placing in the refrigerator for 1 hour, add the solution in beaker b drop by drop into each of the above culture dishes with a dropper, continue to react at 4℃ for 12 hours, then wash after ultrasonication and dry.
[0049] 4. Cut a small piece from the prepared sample, stick it on a carbon tape, spray gold, and place it in a field emission scanning electron microscope to observe the morphology of the in-situ grown polypyrrole conductive layer on the coaxial fiber surface. Figure 4 As shown in the figure, in the absence of dopamine doping, there is no structure on the fiber surface. As the concentration of DA monomer increases, the polymer structure on the fiber surface changes significantly, from irregular particles to rice grains, and then to thorn-like structures and stabilizes, with many free polypyrrole fibers appearing. The prepared composite conductive fiber membrane was tested for conductivity, as shown in the figure. Figure 5As shown, it is shown that the conductivity is directly related to the morphology change.
[0050] Example 4: Removal of the protonic acid environment provided by hydrochloric acid in the oxidant as a comparison
[0051] 1. First, 6g of polyurethane was dissolved in a mixed solvent of 18g of N,N-dimethylformamide (DMF) and 18g of tetrahydrofuran (THF) to form a uniform spinning solvent with a solid content of 14wt%; 10g of polyethersulfone was dissolved in a mixed solvent of 27g of N-methylpyrrolidone (NMP) and 9g of tetrahydrofuran (THF) to form a uniform spinning solvent with a solid content of 20wt%. Under the spinning conditions of 15kv voltage, 0.001mm / s pushing speed and 7cm receiving distance, a spinning fiber membrane with an average thickness of 150μm was obtained.
[0052] 2. Weigh 0.06 g of dopamine hydrochloride and place it in beaker a containing 20 mL of deionized water to dissolve, add a magnet and stir on a magnetic stirrer until the solid is completely dissolved; then add 280 μL of pyrrole monomer to the above solution, and stir magnetically again until the solid is completely dissolved; finally, cut a 2*2 cm electrospun membrane and place it in a culture dish, add the solution in beaker a to completely soak it, and place it in a 4°C refrigerator for 12 hours.
[0053] 3. Dissolve 2.5g of ferric chloride hexahydrate in beaker b containing 20mL of deionized water and stir magnetically until it is completely dissolved. After placing in the refrigerator for 1 hour, add the solution in beaker b dropwise into the above culture dish with a dropper and continue to react at 4℃ for 12 hours, then wash it after ultrasonication and dry it.
[0054] 4. Cut a small piece from the prepared sample, stick it on a carbon tape, spray gold, and place it in a field emission scanning electron microscope to observe the morphology of the in-situ grown polypyrrole conductive layer on the coaxial fiber surface, such as Figure 8 (i) and use molecular dynamics to simulate the effect of acidic conditions on the growth of the conductive phase, such as Figure 8 (ii) No acidic conditions, (iii) Acidic conditions. The varistor grown in a hydrochloric acid-free environment will have problems such as macroscopic conductive phase shedding (slag falling off). The above are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without any creative work are within the scope of protection of the present invention.
Claims
1. A piezoresistive sensor based on coaxial electrospinning matrix grafted with thorny polypyrrole conductive phase, comprising a piezoresistance layer, an electrode layer and a packaging layer, characterized in that: The pressure-sensitive layer is a conductive fiber membrane obtained by in-situ grafting of a thorny polypyrrole conductive phase based on dopamine chemical grafting growth on a micron fiber membrane substrate; the micron fiber membrane is prepared by coaxial electrospinning; The micron fiber membrane matrix is prepared by coaxial electrospinning with an elastomer as the outer shell and a high Tg polymer as the inner core; the elastomer includes thermoplastic polyurethane, polydimethylsiloxane PDMS, and Ecoflex, and the high Tg polymer is one or more of polyethersulfone and polyimide.
2. The piezoresistive sensor based on coaxial electrospinning matrix grafted with thorny polypyrrole conductive phase according to claim 1, characterized in that: The coaxial electrospinning is: Every 6-10g of polyurethane elastomer is dissolved in a mixed solvent of 20g of N,N-dimethylformamide and 20g of tetrahydrofuran by an ultra-speed mixer to form a first uniform spinning solution with a solid content of 14-20wt%, and every 10-12g of high Tg polymer is dissolved in a mixed solvent of 30g of N-methylpyrrolidone and 10g of tetrahydrofuran by an ultra-speed mixer to form a second uniform spinning solution with a solid content of 17-25wt%; under the spinning conditions of a voltage of 12-20kv, a pushing speed of 0.001-0.003mm / s, and a receiving distance of 7cm, the first uniform spinning solution is used as the outer shell, the second uniform spinning solution is used as the inner core, and a coaxial needle is used to obtain a micron fiber membrane with an average thickness of 100-300μm.
3. The piezoresistive sensor based on coaxial electrospinning matrix grafted with thorny polypyrrole conductive phase according to claim 1, characterized in that: The preparation method of the conductive fiber membrane is as follows: Dopamine was dissolved in deionized water, and then pyrrole monomer was added, and magnetic stirring was performed until all the solution was dissolved to obtain solution a, which was placed in an environment of 0-6°C for 5 minutes; Take the micron fiber membrane and soak it in solution a. After it is completely soaked, place it in an environment of 0-6°C for 8-16 hours. Then add ferric chloride powder into deionized water, stir it magnetically until it is completely dissolved, add a certain amount of hydrochloric acid solution and continue stirring for 30 minutes. After standing in an environment of 0-6°C for at least 1 hour, obtain solution b. Under low temperature conditions, solution b is added dropwise into solution a, and the reaction is continued at 4-5°C for at least 12 hours. The fiber membrane after the growth of the conductive phase is then cleaned by ultrasonication and dried.
4. The piezoresistive sensor based on coaxial electrospinning matrix grafted with thorny polypyrrole conductive phase according to claim 3, characterized in that: The molar ratio of the dopamine monomer to the pyrrole monomer is 2:1, and the molar ratio of the ferric chloride to the pyrrole monomer is 2:
5.
5. The piezoresistive sensor based on coaxial electrospinning matrix grafted with thorny polypyrrole conductive phase according to claim 4, characterized in that: The concentration of the dopamine monomer is 0.02 mol / L, the concentration of the pyrrole monomer is 0.2 mol / L, and the concentration of the hydrochloric acid is 2 mol / L.
6. The piezoresistive sensor based on coaxial electrospinning matrix grafted with thorny polypyrrole conductive phase according to claim 1, characterized in that: The conductivity of the conductive fiber membrane is in the range of 0.1-2S / m.
7. The piezoresistive sensor based on coaxial electrospinning matrix grafted with thorny polypyrrole conductive phase according to claim 1, characterized in that: The thickness of the conductive fiber membrane is 0.1-0.3 mm.
Citation Information
Patent Citations
Non-tacky, high elastic mono and multifilament polyester polyurethane yarns, process for their production by melt spinning and their uses
EP0629721A2
KR20230098471A